Metallization of leaf-derived lignocellulose scaffolds for high-performance flexible electronics and oligodynamic disinfection - Rakesh Rajendran Nair; Mihai Nita-Lazar; Valeriu Robert Badescu; Cristina Iftode; Jakob Wolansky; Tobias Antrack; Hans Kleemann; Karl Leo (npj Flexible Electronics)
Abstract Vascular tubules in natural leaves form quasi-fractal networks that can be metallized. Traditional metallization techniques for these lignocellulose structures are complex, involving metal sputtering, nanoparticle solutions, or multiple chemical pretreatments. Here we present a novel, facile, and reliable method for metallizing leaf-derived lignocellulose scaffolds using silver microparticles. The method achieves properties on-par with the state-of-the-art, such as broadband optical transmittance of over 80%, sheet resistances below 1 Ω/sq., and a current-carrying capacity exceeding 6 A over a 2.5 × 2.5 cm² quasi-fractal electrode. We also demonstrate copper electrodeposition as a cost-effective approach towards fabricating such conductive, biomimetic quasi-fractals. Additionally, we show that these metallized structures can effectively eliminate pathogenic microorganisms like fecal coliforms and E. coli, which are bacterial indicators of microbiological contamination of water. We finally show that these oligodynamic properties can be significantly enhanced with a small externally applied voltage, indicating the noteworthy potential of such structures for water purification and pollution control.